Maternal serum alpha‐fetoprotein at 12, 22 and 32 weeks' gestation in screening for pre‐eclampsia. (8th March 2016) - Bredaki, F. E.; Mataliotakis, M.; Wright, A.; Wright, D.; Nicolaides, K. H.
ABSTRACT: Objective: To examine the distribution of maternal serum alpha‐fetoprotein (AFP) at 12, 22 and 32 weeks' gestation in singleton pregnancies which develop pre‐eclampsia (PE) and examine the performance of this biomarker in screening for PE. Methods: Serum AFP was measured in 17 071 cases at 11–13 weeks, in 8583 cases at 19–24 weeks and 8609 cases at 30–34 weeks' gestation. Bayes' theorem was used to combine the a‐priori risk from maternal characteristics and medical history with AFP. The performance of screening for PE requiring delivery < 32, at 32 + 0 to 36 + 6, < 37 and ≥ 37 weeks' gestation was estimated. Results: In pregnancies that developed PE, serum AFP multiples of the median (MoM) was increased at 11–13 and 19–24 weeks' gestation, but not at 30–34 weeks, and the values were inversely related to gestational age at delivery. Combined screening with maternal factors and serum AFP improved the prediction provided by maternal factors alone for PE delivering < 37 weeks, but not for PE delivering ≥ 37 weeks. The performance of screening for preterm PE was better at 19–24 weeks than at 11–13 weeks and the detection rate (DR) for a given false‐positive rate (FPR) was higher for PE delivering < 32 weeks than for PE delivering at 32 + 0 to 36 + 6 weeks. The DRs, at 10% FPR, of combined screening at 11–13 weeks for PE delivering < 32 and at 32 + 0 to 36 + 6 weeks were 54% and 45%, respectively, and these improved to 72% and 53% with screening at 19–24 weeks. Conclusions: Measurement of serum AFP at 11–13 and 19–24 weeks' gestation improves the prediction of preterm PE provided by maternal factors alone. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.